“Por el pancho y la coca”. Apuntes sobre las representaciones del trabajo entre los policías de la provincia de Buenos Aires - Garriga Zucal, Jose Antonio (2014)
In this paper we analyze two representations of police-work among policemen of the province of Buenos Ai-res, focused on selflessness and sacrifice. We will show that these notions mobilize self-presentation strategies that are intended to evaluate the world of policemen and their relationships. Since they stress police duty as both risky and not motivated by profit, sacrifice and selfless-ness are positively valued representations, that are used to stage and define moral practices and representations, contributing to a repertoire of distinction that trace moral boundaries which work as resources that validate the occupation of desired social positions.